SOCIAL, ECONOMIC AND CULTURAL CHANGES OF THE ORAON TRIBE IN THE CONTEXT OF DHANBAD DISTRICT OF JHARKHAND - Gope, Dulal; Kumar, Surendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present research analyzes the social, economic and cultural changes of the Oraon tribe located in Dhanbad district of Jharkhand state. This study examines the changes in the time period from 2000 to 2023. There have been extensive changes in the traditional life of this tribe due to the impact of globalization, urbanization, industrialization and government policies. This research highlights the changes in traditional social structure, economic means, lifestyle, cultural beliefs and cultural inheritance.